Urban Mobility and the Production of Space: Everyday Politics and Infrastructural Power in Makassar, Indonesia (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Urban mobility in Southeast Asia is often framed in policy discourse as a matter of infrastructure provision, modernization, and efficiency. Yet, the everyday experiences of city residents reveal that mobility is deeply shaped by power relations, cultural practices, and contested rights to urban space. This paper examines the politics of mobility in Makassar, Indonesia, drawing on Henri Lefebvre’s theory of the production of space and James C. Scott’s notion of infrapolitics to analyze how infrastructures both structure inequality and generate everyday forms of resistance. The study employed an urban ethnographic approach, combining participant observation, in-depth interviews with drivers, commuters, and fisher households, shadowing and time–space diaries, and document analysis of urban planning policies. Fieldwork was conducted in Makassar between January and August 2024, focusing on neighborhoods, terminals, and transport hubs affected by infrastructural change. Findings reveal four interrelated dynamics. First, infrastructural development produces new exclusions, privileging elites and commercial interests while marginalizing informal transport systems and low-income residents. Second, residents engage in everyday tactics and infrapolitics from flexible pete-pete routes to informal market spaces that resist displacement and reclaim access. Third, infrastructures carry symbolic meanings, celebrated by elites as markers of modernity but interpreted by residents as signs of exclusion or resilience. Finally, infrastructure embodies material politics, embedding inequalities and capital priorities into the spatial fabric of the city. The study concludes that mobility in Makassar is not simply about circulation but about contested rights to the city, where infrastructures function simultaneously as instruments of domination and arenas of everyday negotiation. Recognizing these dynamics calls for inclusive urban planning that integrates informal systems, values cultural practices, and prioritizes social equity alongside technical efficiency